Lietuvos 1940-2000 metų spaudos oficialieji statistikos šaltiniai - Šarlauskienė, Angelė (Knygotyra, 2003)
The official subject of Lithuanian publishing statistics, responsible for the direct arrangement of information for all publishing production, is Chamber of Book of Lithuania. It worked from 1945 to 1992. From 1992 to nowadays, its arrangements are proceeded by Bibliography and Book Science Center incorporated in area of Martynas Mažvydas National Library of Lithuania. Since 1957 the statistical records of publishing production are being published in continuing edition "Lithuanian Publishing Statistics" which defines the statistical records of non-periodical and serial documents. Up to now, however, these data do not reflect the comprehensive content and still lack the chronological description. Despite the fact, that since 1957 these data were compiled by Department of Statistics to the Government of Republic of Lithuania and published in general and special editions, making the comparison with primary publications, they are not so consistent and comprehensive. Besides, one should accept, that the official recordings of statistical data are defined only in the area of the private matters of the country, which is directly responsible for such information. In other words, such information is not so far internationally defined. However, one should also accept, that there still exist the traditional mode of delivering of information, which can be simply printed on the sheet of paper. Therefore, in order to find the way for bypassing such obstacles, one may possess the data of statistical records which may provide all possible information for these aspects. Nevertheless, up to now some data are presented only in the general form, which, for instance, reflect only the number of titles and provide no any information of the copies number. It could happen so that one will be unable to get the comprehensive information of the documents based not only on the specified but also on the general attributes. Finally, it could be so, that for all non-periodical publication only the traditional book productions will have the comprehensive statistical analysis.